Bianchi Type-I Cosmological Models for Biharmonic Particles and its Transformations in Spacetime - Körpınar, Talat; Turhan E. (Springer New York LLC, 2014)
In this article, we study timelike biharmonic particles in Bianchi type-I (B-I) cosmological model spacetime. We give a geometrical description of timelike biharmonic particle in spacetime. Moreover, we obtain transformations this particles. Some physical and geometric behaviour of these particles are also discussed in Bianchi type-I (B-I) cosmological model spacetime. © 2014, Springer Science+Business Media New York.
Keywords: Bianchi type-I (B-I) cosmological model; Bienergy; Biharmonic Particle; Energy; Transformations